Demographic information and clinical presentation of victims in Phase III non-inferiority clinical trial of SnaFab compare to Razi antivenom in snakebites. - Seyed Reza Mousavi (13223324) (2025)
Demographic information and clinical presentation of victims in Phase III non-inferiority clinical trial of SnaFab compare to Razi antivenom in snakebites.